Automatação da rega de superfície com retorno, em tempo real, da informação do campo - Shahidian, Shakib (2014)
Os sistemas de rega de superfície, como por exemplo o cabo-rega, apresentam a vantagem de custo de instalação e bombagem reduzido. No entanto, as suas vantagens económicas têm sido erodidas pelo aumento dos encargos com a mão-de-obra, e subsídios à aquisição de equipamentos de rega mais caros. Os avanços tecnológicos dos últimos anos permitem conceber sistemas de rega de superfície automatizados que minimizam a necessidade de mão-de-obra, sem aumentar significativamente os custos. Pretende-se com o presente trabalho dar um contributo para o desenvolvimento de sistemas cabo-rega automatizados, com retorno de informação do campo, que possam optimizar a rega com um mínimo de supervisão. Nesse sentido, foram desenvolvidos sistemas de cabo-rega electrónicos com controlo simples, (CaboMatic), onde a velocidade do deslocamento do êmbolo é introduzida pelo operador. e sistemas de controlo inteligentes, tipo CaboGest, onde o controlador adapta o deslocamento do êmbolo aos comprimentos dos sulcos e às condições de infiltrabilidade do solo, utilizando para o efeito a equação da infiltração determinada em tempo real. Foi também desenvolvido o equipamento necessário à automação e melhor funcionamento do sistema. incluindo um êmbolo auto-solta, sensores de avanço via rádio, e relés que permitem o arranque e paragem automática da rega. O programa original da gestão de rega (CaboGest) sofreu diversas melhorias ao nível do algoritmo de cálculo e gestão global da rega. Foram acrescentadas rotinas de controlo da rega, e uma melhor interface com o operador. Foi desenvolvida uma versão do programa, que simula a rega partindo do último sulco do campo para o primeiro, conseguindo assim aumentar a Eficiência de aplicação. EA. Nesta versão, aquando da simulação do avanço num determinado sulco, o programa já possui e utiliza os tempos de aplicação nos sulcos a jusante que irão influenciar a rega no referido sulco. Passa também a ser possível ao controlador verificar a evolução da rega em pontos múltiplos, criteriosamente seleccionados no campo. Foram controladas 43 regas, constatando-se que os tempos de avanço simulados pelo controlador apresentam um desvio padrão de 10,7 minutos face aos observados. A EA diminuiu ao longo da campanha, passando de 84 para 70% ao fim de trinta regas. A Uniformidade de distribuição, UD variou entre 72 e 90%. Assistiu-se à diminuição gradual da infiltrabilidade, tendo o controlador reduzido a duração total da rega de 30 para 10 horas perto do fim da campanha. Ficou demonstrada a necessidade do controlo em tempo real das condições da infiltrabilidade do solo, bem como da necessidade do re-ajustamento dos módulos parcelares à redução da infiltrabilidade do solo. Constatou-se também que os parâmetros da equação de infiltração determinados pelo método dos dois pontos são influenciados pelo comprimento dos troços considerados e pelo teor de água no solo, sendo insensíveis ao módulo parcelar utilizado. Os sistemas CaboGest desenvolvidos permitem um bom nível de automação com uma qualidade de rega superior ao possível com o controlo manual. Os custos do controlador são compensados em economia de mão-de-obra e uma utilização mais fiável, sendo potencialmente um dos sistemas de rega mais económicos. /Abstract - Automation of surface irrigation with real-time feed-back from the field Surface irrigation systems, such as cablegation offer low installation and pumping costs. Never the less, their economic advantage has been eroded in the past few years by an increase in labor costs along with substantial subsidies to acquisition of more expensive irrigation equipment. The technological advances of the past few years open the doors for automated surface irrigation systems that minimize labor needs, without significantly increasing the operating costs. The main objective of this work is to contribute to the development of automated cablegation systems with feed-back from the field that can offer high irrigation qualities, while minimizing the need for labor and general supervision, . For this purpose electronic cablegation systems were developed with simple controllers (Cabomatic), in which the piston displacement speed is defined by the user, and with intelligent controllers with feed-back (CaboGest) in which the controller adapts the displacement of the piston to the individual length of the furrow and the soil infiltrability. In order to do this, the systems, determines the infiltration equation (Kostiakov type), in real-time, using advance times to two points in a selected furrow. It then proceeds to simulates the advance in each one of the furrows, and thus, using the simulations, efficiently irrigates the field. In order to further automate the system and increase its reliability, a set of auxiliary equipment was developed including an auto-release piston, wireless advance detectors and relays that make it possible to automate the start and end of the irrigation event and to control water supply from the controller. The original irrigation modeling and control program, CaboGest, was submitted to various improvements in terms of the model as well as the overall irrigation management. New irrigation control routines as well as a better user interface were added. A new version of the software was developed (version 3i) that simulates the irrigation from the last to the first furrow, thus improving the overall Application Efficiency, AE. In this version, when the program is simulating the advance in a certain furrow it takes into account the application times for the following furrows which in effect influence the irrigation in the current furrow. In addition, new routines were developed to allow the controller to verify the evolution of the irrigation event in multiple pre-selected points in the field. Thus it is able for the controller to re-adjust the application times accordingly. A total of 43 irrigation events were controlled in three years. The simulated advance times differed from the observed times by an average of 2 min with a standard deviation of 10.7 min, which are satisfactory. The AE decreased along the irrigation season, changing from 84% to 70% after 30 irrigation events. However it was not possible to establish a pattern for the Distribution Uniformity, DU, which varied between 72% and 90%. A sharp decrease in infiltrability was observed along the season, which led the controller to automatically decrease the total irrigation time from 30 hours to about 10 hours at the end of the season. Thus proving that real-time control of the soil infiltrability conditions is crucial in obtaining a high AE. It also became apparent that it is necessary to re-adjust the opening of the gates according to the soil infiltrability, two or three times during the season. The parameters of the Kostiakov infiltration equation, determined by the two point method, are apparently influenced by the length of the furrow and the relative position of the two points considered. On the other hand, the equation is influenced by soil moisture content, while remaining fairly insensitive to the inflow rate. It is possible to conclude that the CaboGest systems developed allow for a high level of automation with better irrigation qualities than is possible with manual control. The cost of the controller is easily repaid by savings in labor and through higher reliability. This is probably one of the most economical irrigation systems available.